2012
DOI: 10.31258/jnat.12.2.167-172
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of organic wastes and their potential use for acid mine drainage remediation

Abstract: Organic substrate is an important component of biological treatments for acid mine drainage (AMD) remediation systems. It provides organic substrates to sulfate-reducing bacteria (SRB) in the sulfate (SO4) reduction, resulting in increased alkalinity and metal sulfide precipitates. Natural organic matters vary in their characteristics, and therefore may perform differently for remediation properties. This study was aimed to characterize four locally available organic wastes (bark, empty fruit bunch, sawdust, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 12 publications
1
9
0
1
Order By: Relevance
“…This means that the substrates in the growth media had played important role in raising the pH, regardless the planting treatments. Such observations have been reported by various studies (Waybrant et al, 1998;Gibert et al, 2004;Zagury et al, 2006;Sheoran, 2006;Munawar & Riwandi, 2010). Alkaline manure and sludge contained in the growth media might have contributed their alkalinity to the system.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…This means that the substrates in the growth media had played important role in raising the pH, regardless the planting treatments. Such observations have been reported by various studies (Waybrant et al, 1998;Gibert et al, 2004;Zagury et al, 2006;Sheoran, 2006;Munawar & Riwandi, 2010). Alkaline manure and sludge contained in the growth media might have contributed their alkalinity to the system.…”
Section: Resultssupporting
confidence: 75%
“…This agrees with a study by Sheoran (2006), who found significant pH increases (from around 3 to more than 7 in a wetland system using wood chips and goat manure. In a previous study we also found that organic wastes containing high alkalinity (high pH) and nutrient concentrations (chicken manure) improved AMD quality, through increasing its pH above 6 (Munawar & Riwandi, 2010). Drastic increase from pH 2.8 of the original AMD to more than 6 occurred 24 hours after treatment application.…”
Section: Resultsmentioning
confidence: 73%
“…Pirit yang teroksidasi jika terlarut dalam air akan membentuk SO4 2-dan meningkatkan kemasaman. Reaksi oksidasi tersebut terjadi secara biologi oleh bakteri Thiobacillus thiooxidans yang dapat menghasilkan asam sulfat dan menurunkan nilai pH perairan (Munawar dan Riwandi, 2010).…”
Section: Pendahuluanunclassified
“…Temperature, humidity, salinity, pH, nutrition, carbon dioxide, oxygen, substrate concentration, surfactant, etc. would affect the degradation [ 91 , 92 , 93 , 94 ]. Bacteria or their enzymes needed a suitable temperature, pH and substrate concentration [ 95 ].…”
Section: Research On the Progress Of Microbial-degradation Of Pestmentioning
confidence: 99%
“…There was a comparison of cell’s surface hydrophobicity of strain L12 in xylene and n-octanol [ 79 ]. The hydrophobicity of bacterial cell’s surface was one of the most important determinants of nonspecific bacterial adhesion of bacteria to variously biological and abiotic surfaces and interfaces, and it was also one of the main elements that affected bacterial uptake and the degradation of hydrophobic organic matter [ 93 ]. It had important significance of studying the cell’s surface hydrophobicity to degrade organic compounds in non-aqueous phase.…”
Section: Microbial Degradation Of Cy and Its Applicationmentioning
confidence: 99%